2017
DOI: 10.1007/s00383-017-4135-y
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors indicating survival with native liver after Kasai procedure for biliary atresia

Abstract: The BDP ratio is a better prognostic indicator than PCK7 in BA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 18 publications
1
6
0
2
Order By: Relevance
“…Патоморфологическое исследование биоптатов печени является наиболее чувствительным и досто-верным методом ранней диагностики билиарной атрезии, что имеет большое значение для успешного исхода оперативного лечения. Такого мнения придерживаются многие авторы [16,33,35,36,37,38].…”
Section: диагностикаunclassified
“…Патоморфологическое исследование биоптатов печени является наиболее чувствительным и досто-верным методом ранней диагностики билиарной атрезии, что имеет большое значение для успешного исхода оперативного лечения. Такого мнения придерживаются многие авторы [16,33,35,36,37,38].…”
Section: диагностикаunclassified
“…The PCK7 was the only studied parameter associated with 1-year native liver survival, independently of age and fibrosis score. In a Japanese study, Obayashi et al [ 88 ] reviewed 32 biliary atresia patients undergoing hepatoportoenterostomy operation from 1976 to 2016 with more than five portal canals in biopsy samples. These authors confirmed our original study with relevance of BD/PT ratio [ 8 , 88 ].…”
Section: Treatmentmentioning
confidence: 99%
“…In a Japanese study, Obayashi et al [ 88 ] reviewed 32 biliary atresia patients undergoing hepatoportoenterostomy operation from 1976 to 2016 with more than five portal canals in biopsy samples. These authors confirmed our original study with relevance of BD/PT ratio [ 8 , 88 ]. Obayashi et al The study [ 8 , 88 ] suggests that the mean BDP ratio, i.e., the number of the bile ducts in portal canal ratio may be a better short-term prognostic indicator than PCK7.…”
Section: Treatmentmentioning
confidence: 99%
“…The diagnosis and treatment of BA should not be delayed since its prognosis depends on timely and effective treatment 4 . Roux-en-Y hepatic portoenterostomy or Kasai procedure is the technique of choice as a palliative treatment 5,6 . The age at which this surgery is performed is the most important prognostic factor for survival; for example, it is estimated that 60% of cases intervened within the first 90 days of extrauterine life will restore bile flow.…”
Section: Introductionmentioning
confidence: 99%